The Ba2+ block of the ATP-sensitive K+ current of mouse pancreatic beta-cells. - Takano, M; Ashcroft, F (1996)
We studied the block of whole-cell ATP-sensitive K+ (KATP) currents in mouse pancreatic beta-cells produced by external Ba2+. Ba2+ produced a time-and voltage-dependent block of KATP currents, both the rate and extent of the block increasing with hyperpolarization. With 5.6 mM [K+]o, the relationship between the steady-state KATP current and [Ba2+]o was fit by the Hill equation with a Kd of 12.5 +/- 2.8 microM at -123 mV and of 0.18 +/- 0.02 mM at -62 mV. The Hill coefficient (n) was close to 1 at all potentials indicating that binding of a single Ba2+ ion is sufficient to block the channel. When [K+]o was raised to 28 mM the Kd was little changed (12.4 +/- 4.1 microM at -123 mV, 0.27 +/- 0.05 mM at -62 mV) and n was unaffected, suggesting that K+ does not interact with the Ba2+ binding site. The kinetics of Ba2+ block were slow, 10 microM Ba2+ blocking the KATP current with a time constant of 20 ms at -123 mV in 28 mM [K+]o. The blocking rate constant was calculated as 1.7 mM-1ms-1 and the unblocking rate as 0.02 ms-1, at -123 mV. The data are discussed in terms of a model in which Ba2+ binds to a site at the external mouth of the channel to inhibit the KATP channel.